EFFECT OF FEEDING VARIOUS LEVELS OF CANOLA MEAL ON THE PERFORMANCE OF BROILER CHICKS - M. Z. Naseem; S. H. Khan; M. Yousaf (Journal of Animal and Plant Sciences, 2006)
A total of 1905 mixed sex day old broiler chickens were reared in environmentally controlled house for 5 weeks to study the production performance of chicks by feeding different levels of canola meal in their diets. The chickens were randomly allocated to five dietary treatment groups ( A, B, C, D and E ) having three replicates of 127 birds in each group. Groups A, B, C, D and E were fed pelleted diets containing 5, 10, 15, 20 and 25 percent canola meal (with 85% KOH solubility and 36% crude protein), respectively. Experimental diets and fresh water were offered ad libitum. Feed intake during 0-35 days of age was reduced (P< 0.01) in chickens fed diets with increasing level of canola meal. Weight gain and feed utilization efficiency was better (P< 0.01) in chickens fed diet containing 25% canola meal compared to all other treatment groups. Dressed carcass weight and other slaughtering parameters of chickens among all treated groups were found to be similar (P>0.05). The price per kilogram weight gain to market age was lowest in diet containing high level of canola meal indicating maximum inclusion of canola meal in broiler diet is economical. It may be suggested that canola meal (with 85% KOH solubility) upto 25% can be incorporated in broiler diets without any adverse effect on production parameters. For optimizing the profits from feeding of canola meal, it may be used upto 25% in the diets of commercial broiler chicks.
Keywords: Canola meal; broiler chicks; performance; carcass percentage.